Mid- to late Holocene sea-level rise recorded in Hells Bells 234U/238U ratio and geochemical composition - Schorndorf, Nils; Frank, Norbert; Ritter, Simon M.; Warken, Sophie F.; Scholz, Christian; Keppler, Frank; Scholz, Denis; Weber, Michael; Aviles Olguin, Jeronimo; Stinnesbeck, Wolfgang (Scientific reports, 2023)
Hells Bells are underwater secondary carbonates discovered in sinkholes (cenotes) southeast of Cancun on the north-eastern Yucatán peninsula, Mexico. These authigenic calcite precipitates, reaching a length of up to 4 m, most likely grow in the pelagic redoxcline. Here we report on detailed 230Th/U-dating and in-depth geochemical and stable isotope analyses of specimens from cenotes El Zapote, Maravilla and Tortugas. Hells Bells developed since at least ~ 8000 years ago, with active growth until present day. Initial (234U/238U) activity ratios (δ234U0) in Hells Bells calcite decreas from 55 to 15‰ as sea level converges toward its present state. The temporal evolution of the geochemistry and isotope composition of Hells Bells calcites thus appears to be closely linked to sea-level rise and reflects changing hydrological conditions (desalinization) of the aquifer. We suggest that decelerated leaching of excess 234U from the previously unsaturated bedrock traces Holocene relative sea-level rise. Considering this proxy, the resulting mean sea-level reconstruction contains half as much scatter, i.e. improves by a factor of two, when compared to previously published work for the period between 8 and 4 ky BP.
Veröffentlicht: 20. Juni 2023
Gesehen am 27.10.2023
Im Titel sind die Zahlen 234 und 238 hochgestellt